The 2nd International Conference on Water Resource and Environment (WRE 2016). Issue 2 (November 2016) - Liu, Zhouli; Chen, Wei; He, Xingyuan; Yu, Shuai; Ding, Weihang; Liu, Jianjun; Wu, Yuliang; Fan, Kaixiang; Li, Yuanchao; Zheng, Xinqing; Chen, Shiquan; Xie, Haiqun; et al.
Table of contents 01 The eco-toxicological effects of cadmium stress on five ornamental plants Zhouli Liu, Wei Chen, Xingyuan He, Shuai Yu, Weihang Ding 02 Study on the formation and release mechanisms of hydrogen sulfide in Longtan coal mine Jianjun Liu, Yuliang Wu, Kaixiang Fan 03 Coral bleaching in the North Reef of China's Xisha Islands in 2014 Yuanchao Li, Xinqing Zheng, Shiquan Chen, Haiqun Xie 04 Soil chemical characteristics in aCunninghamia lanceolata stand suffering from ice-snow damage Jie Li, Zhuomin Wang, Li Xue 05 Diversity of understory vegetation was under aCunninghamia lanceolata stand suffering from ice-snow damage Zhiyang Lie, Weilong Huang, Tongtong Zhou, Li Xue 06 The effect of water, nitrogen and harvesting time on yield and biomass allocation ofHelianthus tuberosus L. Kai Gao, Tiexia Zhu 07 The vertical variation of microbial communities in the sediment of sea cucumber pond Weiteng Mao, Pei Yu, Xinfang Lv, Yunchun Li 08 Indicating significances of alpine plant functional groups to environmental change Peixi Su, Rui Shi 09 Research on the daily CH4 fluxes of soil in summer mangrove community at Yingluogang of Guangxi, China Yong Jiang, Xingbin Chen, Shichu liang 10 Beach protection structures in middle and lower reaches of Yangtze River Junfeng Xu 11 Social responsibility management of large dam project with owner as core: an empirical case in China Jiwei Zhu, Zhao Zhai, Linan Zhou, Yun Le, Li Cao 12 The ecological function value assessment analysis of urban waterfront Jiwei Zhu, Ping Lu, Zhiqian Huang, Bei Zhou 13 Mechanism of diurnal osmotic potential changes and adjustment of threeCaragana species in different habitats of the Inner Mongolia Plateau Zhirong Zheng, Shihai Lv, Chaoyang Feng 14 Biodiversity of phytoplankton and environmental influences analysis of Longfeng Wetland, China Nan Song, Yan Liu, Xinxin Lu, Yawen Fan 15 The effect of human activities on culturable soil microbes from Yaoquan Mountain in Wudalianchi, China Jianfei Guan, Jihua Wang, Xueping Zhang